Analisis Pengaruh Kepemilikan Saham dan Struktur Modal terhadap Profitabilitas: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Periode 2020-2022 - Muhammad Abyan Shafly; Suyatmin Waskito Adi (Economic Reviews Journal, 2024)
This research aims to empirically test the influence of share ownership, namely institutional share ownership (INST) and managerial share ownership (MAN) as well as capital structure (DER) both partially and simultaneously on profitability. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2020-22 using an annual period. The sample used in this research was 35 manufacturing companies. Where sample selection was carried out using the purposive sampling method. The type of data used in this research is quantitative research, namely where the data used is secondary data. Secondary data is data obtained indirectly but can be published through intermediary media. Secondary data in this research comes from annual financial reports. The data analysis technique used in this research is multiple linear regression. Based on the results of data processing, it shows that institutional share ownership and managerial share ownership have no effect on profitability. Meanwhile, capital structure influences profitability.